HLA-associated preadaptation in HIV Vif is associated with higher set point viral load and faster CD4+ decline in Zambian transmission pairs. (1st July 2021) - Connolly, Sarah; Carlson, Jonathan M.; Schaefer, Malinda; Bere, Alfred; Kilembe, William; Allen, Susan; Hunter, Eric
Abstract : Objective (s): We investigated the relationship between human leukocyte antigen (HLA)-associated preadaptation for the entire subtype C HIV-1 proteome of the transmitted founder virus and subsequent HIV-1 disease progression in a cohort of heterosexual linked transmission pairs in Zambia. Design: An adaptation model was used to calculate an adaptation score for each virus-HLA combination in order to quantify the degree of preadaptation of the transmitted virus to the linked recipient's HLA alleles. These scores were then assessed for their relationship to viral load and longitudinal CD4 + decline in the recipient. Methods: Viral RNA was extracted from the plasma of the donor partner and the linked recipient near the time of transmission, as well as longitudinally from the linked recipient. Viral adaptation scores were calculated for each individual and each protein in the subtype C HIV-1 proteome. Results: The majority of HLA-associated sites were located in Gag, Pol and Nef; however, proportional to protein length, the accessory and regulatory proteins contained a relatively high proportion of HLA-associated sites. Over the course of infection, HLA-mediated immune adaptation increased for all proteins except Vpu and gp120. Preadaptation was positively associated with higher early set point viral load and faster CD4 + decline. When examined by protein, preadaptation in Pol and Vif were statistically significantly associated with these markers of disease progression. Conclusion: Adaptation in Pol had the greatest impact on viral control. Despite containing a large proportion of HLA-associated sites, Vif was the only regulatory or accessory protein for which preadaptation significantly correlated with disease progression. Abstract : Supplemental Digital Content is available in the text